2007
DOI: 10.1530/eje-06-0727
|View full text |Cite
|
Sign up to set email alerts
|

Posterior pituitary function in Sheehan’s syndrome

Abstract: Objective: We studied posterior pituitary function in 27 patients with Sheehan's syndrome and 14 controls. Design: All patients were investigated by water deprivation test and 26 of them by 5% hypertonic saline infusion test. None of the patients had symptoms of diabetes insipidus and all patients were on adequate glucocorticoid and thyroid hormone replacement therapy before testing. Results: According to dehydration test, 8 (29.6%) patients had partial diabetes insipidus (PDI group) and 19 (70.3%) had normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Although clinically manifest diabetes insipidus is uncommon in SS, the frequency of partial diabetes insipidus was found to be 29.6% in SS patients who did not have polyuria (28). In that study the osmotic threshold for the onset of thirst in patients with SS was found to be increased.…”
Section: Discussionmentioning
confidence: 74%
“…Although clinically manifest diabetes insipidus is uncommon in SS, the frequency of partial diabetes insipidus was found to be 29.6% in SS patients who did not have polyuria (28). In that study the osmotic threshold for the onset of thirst in patients with SS was found to be increased.…”
Section: Discussionmentioning
confidence: 74%
“…We further evaluated causes of hypopituitarism and considered only cases where posterior pituitary damage was likely. 30,31 The following cases were excluded: subclinical hypopituitarism (n ¼ 16); 4,6,8,11 -13,17,19,25,28,29 cause of hypopituitarism not specified (n ¼ 1); 21 first-trimester miscarriages (n ¼ 15). 1,4,12,19 Sixteen case reports 3,5-7,9,10,14 -16,18,20,22-24,26,27 describing the outcome of 18 pregnancies and one trial 1 reporting 13 pregnancies in nine women were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…None of the patients in the present se ries had involvement of posterior pituitary function in the form of polyuria. Diabetes insipidus is quite rare in these patients, though subtle features of posterior pituitary involvement have been reported (23). Table 3 summarizes the anterior pituitary involvement in re ported series of patients with SS.…”
Section: Discussionmentioning
confidence: 99%